Graduate students appreciate Google Scholar, but still find use for libraries. Issue 3 (27th May 2014) - Wu, Ming-der; Chen, Shih-chuan
Abstract : Purpose: – The purpose of this study is to examine how graduate students perceive and use Google Scholar. Google Scholar has provided a convenient alternative for finding scholarly documents since its inception in 2004 and has become a favoured tool for numerous academics. Knowledge of patrons' usage patterns and attitudes towards Google Scholar will assist librarians in designing appropriate instruction programmes to improve students' research abilities. Design/methodology/approach: – In this study, 32 graduate students from the National Taiwan University were interviewed whose fields of study are the humanities (10), social sciences (11) and science and technology (11). Findings: – Students prefer the usability of Google Scholar over library databases. However, they appreciate the quality of documents retrieved from library databases and regard these databases as crucial tools for finding scholarly documents. Science and technology students favoured Google Scholar more than those who study the humanities and social sciences. Research limitations/implications: – This study only examines the perceptions and behaviour of graduate students. Future studies should include undergraduate students to investigate their use of Google Scholar, thereby obtaining a comprehensive understanding of various patrons of university libraries. Practical implications: – This study shows that graduate students appreciate and use Google Scholar to find scholarly documents, although some students experience difficulties. The findings of this study may assist university libraries in improving their instruction programmes. Originality/value: – The majority of previous studies have focused on coverage, quality and retrieval performance of Google Scholar. However, this study evaluates Google Scholar from a user's perspective.